Paracoccidioidomycosis: Current perspectives from Brazil - Mendes, Rinaldo Poncio [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Marques, Sílvio Alencar [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Venturini, James [UNESP]; Sylvestre, Tatiane Fernanda [UNESP]; Paniago, Anamaria Mello Miranda; Pereira, Ana Carla; da Silva, Julhiany de Fátima [UNESP]; Fabro, Alexandre Todorovic [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Bagagli, Eduardo [UNESP]; et al. (Bentham Science Publishers, 2017)
Background: This review article summarizes and updates the knowledge on paracoccidioidomycosis. P lutzii and the cryptic species of P. brasiliensis and their geographical distribution in Latin America, explaining the difficulties observed in the serological diagnosis. Objectives: Emphasis has been placed on some genetic factors as predisposing condition for paracoccidioidomycosis. Veterinary aspects were focused, showing the wide distribution of infection among animals. The cell-mediated immunity was better characterized, incorporating the recent findings. Methods: Serological methods for diagnosis were also compared for their parameters of accuracy, including the analysis of relapse. Results: Clinical forms have been better classified in order to include the pictures less frequently observesiod. Conclusion: Itraconazole and the trimethoprim-sulfamethoxazole combination was compared regarding efficacy, effectiveness and safety, demonstrating that azole should be the first choice in the treatment of paracoccidioidomycosis.
Keywords: Antifungal compounds; Endemic mycosis; Paracoccidioides brasiliensis; Paracoccidioides lutzii; Paracoccidioidmycosis; Systemic mycosis